Development of Portable Solar Electricity Generating System - Awang Zainudin, Awangko Arshaduddin (Universiti Teknologi PETRONAS, 2014)
The project aim is to develop a portable solar electricity generating system. Since Malaysia is located near to the equator, the country receive large and constant amount of solar energy during daytime. It would be a waste if this energy is not utilised for producing electrical energy. The development of solar energy generation system (SEGS) is needed to fully utilise the usage of solar energy received. However, SEGS in Malaysia is still seen as a new concept and research is still being done to produce an efficient and cost-effective SEGS. In this project, study On SEGS is conducted to get a clearer picture of the parameters and condition required to build the best SEGS. In order to have a good SEGS, design of a proper sun-tracking system and the system sizing are required. The measurement of insolation throughout the day is also been done to get a clearer picture for the insolation pattern. Other than that, the comparison for the type of PV modules has also been conducted. This is to ensure the SEGS utilises the best type of PV module. A proper storage system for SEGS is also a crucial part of this project. As Sunlight is only available during the day and the insolation changes throughout the day a proper storage system is required to optimise the usage of the SEGS. The portability of the SEGS has also been discussed in this project. To ensure the maximise usage of SEGS the SEGS has to be portable. Another factor we considered in this project is the price of production of the SEGS. Currently, SEGS is quite pricy. If the cost of production of SEGS can be reduced to a cheaper price, the market demand for the SEGS will increase. This report contains the theoretical background and project activities on completing the SEGS. Analyses of results are further discussed in this report after simulation studies and outdoor experiments are conducted to measure the value of solar insolation.